Indian monsoon variability on millennial-orbital timescales - Kathayat, Gayatri; Cheng, Hai; Sinha, Ashish; Spötl, Christoph; Edwards, R. Lawrence; Zhang, Haiwei; Li, Xianglei; Yi, Liang; Ning, Youfeng; Cai, Yanjun; Lui, Weiguo Lui; Breitenbach, Sebastian (Scientific Reports, 2016)
The Indian summer monsoon (ISM) monsoon is critical to billions of people living in the region. Yet, significant debates remain on primary ISM drivers on millennial-orbital timescales. Here, we use speleothem oxygen isotope (δ18O) data from Bittoo cave, Northern India to reconstruct ISM variability over the past 280,000 years. We find strong coherence between North Indian and Chinese speleothem δ18O records from the East Asian monsoon domain, suggesting that both Asian monsoon subsystems exhibit a coupled response to changes in Northern Hemisphere summer insolation (NHSI) without significant temporal lags, supporting the view that the tropical-subtropical monsoon variability is driven directly by precession-induced changes in NHSI. Comparisons of the North Indian record with both Antarctic ice core and sea-surface temperature records from the southern Indian Ocean over the last glacial period do not suggest a dominant role of Southern Hemisphere climate processes in regulating the ISM variability on millennial-orbital timescales.